Antibodies against complement-regulatory proteins on platelets in immune thrombocytopenia. (19th May 2017) - Unterberger, Ursula; Eichelberger, Beate; Ulz, Anja; Panzer, Simon
Abstract: In immune thrombocytopenia (ITP), antibodies reacting with platelet membrane glycoproteins (GP) mediate premature platelet cleavage, resulting in thrombocytopenia and therefore a risk of bleeding. These antibodies may induce complement activation, thus mediating complement-induced platelet destruction. In this study, we investigated the possibility of an additional complement-related pathogenic mechanism, where antibodies against the complement-regulatory factors CD55 and CD59 may directly interfere with normal complement function. CD55 downregulates both the classic and the alternative activation pathways, while CD59 blocks the formation of the membrane attack complex; both proteins are present on platelets and may therefore be targets of autoantibodies. Using the simultaneous analysis of specific platelet antibodies (SASPA) assay, we found that in some cases of immune-mediated thrombocytopenia, anti-CD55 and -CD59 antibodies are detectable in patients' sera and/or on their autologous platelets in combination with antibodies against platelet-specific GP. Although antibodies against CD55 and CD59 seem to be a rare phenomenon, this finding may have clinical relevance due to the availability of highly effective therapeutics targeting the complement system.